2016
DOI: 10.1515/cclm-2015-0377
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of acute pyelonephritis from other febrile states in children using urinary neutrophil gelatinase-associated lipocalin (uNGAL)

Abstract: uNGAL can be a useful diagnostic biomarker in acute pyelonephritis in children, but also in differentiating cystitis from febrile states other than UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Arambasic et al revealed high uNGAL sensitivity (92.5%) and specificity (91%) for differentiation of APN from other febrile infection. They also showed utility of uNGAL for differentiation of upper from lower UTI [24]. In a similar study, Nicavar et al demonstrated smaller uNGAL sensitivity (76%) and specificity (77%) for distinguishing APN from other febrile infections [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arambasic et al revealed high uNGAL sensitivity (92.5%) and specificity (91%) for differentiation of APN from other febrile infection. They also showed utility of uNGAL for differentiation of upper from lower UTI [24]. In a similar study, Nicavar et al demonstrated smaller uNGAL sensitivity (76%) and specificity (77%) for distinguishing APN from other febrile infections [6].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated usefulness of both biomarkers for predicting and monitoring AKI of diverse etiologies [3, 13, 19, 20]. Recent data show also utility of NGAL and KIM-1 for detecting UTI [12, 21-23] and APN [4, 14, 18, 24] in children and adults. The studies published so far are small in size [5, 6, 21, 25] and results are contentious [26-28].…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested the potential utility of uNGAL as a marker of APN in humans [38]. Since that time, several clinical studies have been conducted for assessing the diagnostic value of uNGAL for detecting APN, but the results are not clear [14, 29, 33, 39]. In children, measurement of urine biomarkers is preferred over blood tests because of the less painful and non-invasive procedure [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is released from activated neutrophils and other immune cells, and reduces bacterial growth in the early stage of infection [24, 25]. Recent reports in the literature demonstrated the utility of NGAL for predicting UTI [25-28] and APN [10, 29, 30] in children and adults. However, the published studies are small so far [2, 9, 27], only limited data are available for infants [1, 2, 5, 9, 31], and results are contentious [14, 32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations of urinary tract infections (UTI) have mainly focused on AMPs in the urine of patients or animal models [12][13][14]. So far, multiple AMPs have been identified in the context of urinary tract immunity, including cathelicidin antimicrobial peptide (LL-37 or CAMP) [15], different α-and βdefensins [16], members of the ribonuclease A superfamily, such as RNase 7 [17], pentraxin-related protein 3 (PTX3) [18], uromodulin (UMOD) [19,20], and metal-binding AMPs, such as lipocalin-2 [20][21][22], lactotransferrin (LTF) [14], and the S100A8/S100A9 heterodimer calprotectin [23][24][25][26]. The urothelium of the bladder and epithelial cells of the kidney and ureter were identified as primary sources for AMPs in the urinary tract, alongside cells of the innate immune system [10,27].…”
Section: Introductionmentioning
confidence: 99%